Facile electrodeposition of reduced graphene oxide hydrogels for high-performance supercapacitors. Issue 14 (13th March 2015) - Pham, Viet Hung; Gebre, Tesfaye; Dickerson, James H.
Abstract : We report the production of reduced graphene oxide hydrogels through the electrodeposition of graphene oxide and their use as electrodes in high-performance supercapacitors. Abstract : We report both a facile, scalable method to prepare reduced graphene oxide hydrogels through the electrodeposition of graphene oxide and its use as an electrode for high-performance supercapacitors. Such systems exhibited specific capacitances of 147 and 223 F g −1 at a current density of 10 A g −1 when using H2 SO4 and H2 SO4 + hydroquinone redox electrolytes, respectively.